Integrating of permaculture system with eco-gamification systems in biodiversity learning to promote SDG-12 - Najira Najira; Saefudin Saefudin; Taufik Rahman; Rahmat Baharuddin; Zuliande Zidan (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
The achievement of biodiversity learning in schools has only reached 60% classical completeness, with low student understanding: 10.1% demonstrated full comprehension, 48.7% experienced misconceptions, and 41.2% showed no conceptual understanding. This highlights the need to improve biodiversity education. This study aims to enhance students' understanding by integrating permaculture systems and eco-gamification into the learning process, aligning with Sustainable Development Goal (SDG) 12 on responsible consumption and production. Using a quantitative experimental design, 25 10th-grade students from a high school in Bandung were selected through cluster sampling. Data were collected via Likert scale questionnaires, expert observation sheets (0–1 scale), and direct observations. The study was conducted in three stages: preparation, implementation, and data analysis. The implementation achieved an 82% success rate (Good category), indicating high student engagement. Student responses showed 48.7% strongly agreed (Fair), 33.1% agreed (Poor), and 18.2% disagreed (Poor), reflecting varying acceptance levels. Key challenges included difficulties in memorizing scientific names and understanding binomial nomenclature. Enhancing strategies, such as hands-on practice and optimized gamification, is essential to maximize learning outcomes while fostering awareness of ecosystem balance.Abstrak. Pencapaian pembelajaran keanekaragaman hayati di sekolah hanya mencapai 60% ketuntasan klasikal, dengan tingkat pemahaman siswa yang rendah: 10,1% menunjukkan pemahaman penuh, 48,7% mengalami miskonsepsi, dan 41,2% tidak memahami konsep sama sekali. Hal ini menunjukkan perlunya peningkatan pendidikan keanekaragaman hayati. Penelitian ini bertujuan untuk meningkatkan pemahaman siswa dengan mengintegrasikan sistem permakultur dan eco-gamification dalam proses pembelajaran, sejalan dengan Tujuan Pembangunan Berkelanjutan (SDG) 12 tentang konsumsi dan produksi yang bertanggung jawab. Penelitian ini menggunakan desain eksperimen kuantitatif dengan melibatkan 25 siswa kelas X dari salah satu SMA di Bandung yang dipilih melalui teknik cluster sampling. Data dikumpulkan melalui kuesioner skala Likert, lembar observasi ahli (skala 0–1), dan observasi langsung. Penelitian dilakukan dalam tiga tahap: persiapan, pelaksanaan, dan analisis data. Implementasi pembelajaran mencapai tingkat keberhasilan sebesar 82% (kategori Baik), menunjukkan tingginya keterlibatan siswa. Respon siswa menunjukkan 48,7% sangat setuju (Cukup), 33,1% setuju (Kurang), dan 18,2% tidak setuju (Kurang), mencerminkan tingkat penerimaan yang bervariasi. Tantangan utama yang dihadapi adalah kesulitan dalam menghafal nama ilmiah dan memahami tata nama binomial. Oleh karena itu, peningkatan strategi seperti praktik langsung dan optimalisasi elemen gamifikasi diperlukan untuk memaksimalkan hasil belajar sekaligus meningkatkan kesadaran menjaga keseimbangan ekosistem.